The Current Trends of Neuropsychological Assessment Implementation in Educational Environment - Valeriya Stepashkina; Alina Akhmetshina (ARPHA Proceedings, 2022)
At present, there is high importance to involve Neuropsychological Assessment in the educational environment. The problematic issue reveals the idea of integrating neuropsychology and personality diagnostics procedure of adolescent and young age people. A new approach to the learning ability assessment should essentially be revealed in the understanding of personal neuropsychological status in adolescence and youth. Personality diagnostics in accordance with Neuropsychological Assessment calls for a multidisciplinary approach for destructive risks identifying in a young personality. The theoretical conceptualization of the problem of personality assessment is a systematic synthesis of modern trends of neuropsychology in the Russian scientific tradition and the world practice of neuropsychological diagnostics in adolescence and youth age. This review of relevant studies is focused on behavioral, personality and affective disorders in terms of neuropsychological basis. Results of this study also consider the cognitive and high mental impairments that accompany dysfunction in personality characteristics. There is a high risk of destructiveness developing and risky behavior forming that complicates the formation of emotional-volitional, motivational and personal spheres. The negative effect of condition in cognitive dysfunctions and personal destruction will generate failure in learning and reduced motivation to learn.